Pengaruh Komunikasi Persuasif dan Personal Branding Celebrity Endorser terhadap Kesadaran Vaksinasi Covid-19 (Analisis Structural Equation Modeling Partial Least Squares) - Naura Fika Azmi Nabilla; Subhan Afifi (Jurnal Mahasiswa Komunikasi Cantrik, 2023)
This research aims to examine the influence of Persuasive Communication and Celebrity Endorser's Personal Branding on the Covid-19 Vaccination Awareness using the Structural Equation Modeling-Partial Least Squares (SEM-PLS) analysis method. The results of the study demonstrate good convergent validity, as indicated by Outer Loading (>0.7) and Average Variance Extracted (AVE) (>0.5), which meet the criteria. Discriminant validity is also confirmed, as each indicator shows favorable correlations according to the Cross Loading values. Additionally, the Fornell Larcker Criterion (HTMT) values indicate high correlations among all constructs. Reliability tests reveal that all constructs exhibit satisfactory reliability, surpassing the criteria with Cronbach's Alpha and Composite Reliability values (>0.7) for each construct. The structural model analysis yields an R-Square value of 42.8%, suggesting that Persuasive Communication and Celebrity Endorser's Personal Branding have a weak influence on Covid-19 Vaccination Awareness. The remaining portion (57.2%) is influenced by factors beyond the scope of this study. The hypothesis testing results indicate a significant impact of Persuasive Communication and Personal Branding on the level of Covid-19 Vaccination Awareness. Path Coefficients demonstrate a positive relationship between Persuasive Communication, Personal Branding, and Covid-19 Vaccination Awareness, with T-Statistic values exceeding 1.96. Persuasive Communication significantly plays a positive role (β = 0.293, p < 0.05), as does Personal Branding (β = 0.397, p < 0.05). This research contributes academically and practically to the utilization of Celebrity Endorsers for public communication strategies in health campaigns.